Pengaruh Pendapatan, Konsumsi Rumah Tangga, dan Sosial Demografi terhadap Kesejahteraan Keluarga Petani Padi di Subak Jatiluwih, Desa Jatiluwih, Kecamatan Penebel, Kabupaten Tabanan - NI NYOMAN SRI BI ADNYANI; MADE ANTARA; PUTU UDAYANI WIJAYANTI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
The Effect of Income, Household Consumption, Social Demographics on the Well-being of Rice Farming Families at Subak Jatiluwih, Desa Jatiluwih, Kecamatan Penebel, Kabupaten Tabanan Farmers have a very important role in all activities in the agricultural sector, therefore farming families must have a prosperous life. There are several factors that affect well-being, namely social demographic characteristics, income, and household consumption. The purpose of this study is to 1) Analyze the influence of demographics on farmer's income 2) Analyze the influence of socio-demography on farmer household consumption 3) Analyze the effect of income on farmer household consumption 4) Analyze social influence on farmer's family well-being 5) Analyze the effect of income on well-being farming family 6) Analyze the effect of household consumption on the well-being of farming families. Collecting data using a closed questionnaire using descriptive analysis methods and SEM-PLS. The results of this study showed a significant effect on all relationship variables specified in the research objectives. Based on the results of the study, suggestions that can be given related to this research are that it is hoped that farmers can take advantage of the socio-demographic characteristics of the family in order to increase the income and well-being of the farmer's family, it is hoped that farmers can increase their income and allocate their income for useful things, and it is hoped that farmers can optimize household consumption and reduce consumption of things they feel are not really needed.